KENDALA PEMASARAN KOPI ARABIKA PADA MASA PANDEMI COVID 19 DI ACEH TENGAH - Fadli Fadli; Hafni Zahara; Emmia Tambarta (Jurnal Bisnis Tani, 2020)
The corona-virus pandemic which has become increasingly massive lately has ultimately disrupted the marketing process to a significant point. This condition will cause various obstacles in the marketing process, including in Gayo Arabica coffe marketing. This study uses an analysis tool. Of USG (Urgency, seriousness, Growth). USG is a tool to prioritize the constraints that must be resolved by determining the level of urgency, seriousness, and development of constraints on a likers scale. These various marketing limitation must be recognized so that a solution can be prepared. The result of the study prove that the marketing limitation coffe during the COVID-19 period based on the level of seriousness include the difficulty of licensing transportation between Indonesia and destination countries, the economic recession experienced by international coffe buyers, the economic condition of coffe exporting companies during the pandemic period, the overall price of green bean coffe beans, and the social distancing conditions that prevailed during the pandemic.  The main abstacle among these constrains is the difficulty in licensing transportation between Indonesia and the destination country, with a score of 14 in the USG analysis. The obstacle that ranks second with a score of 13 in the USG analysis is the economic recession experienced by internasional coffe buyers, and the third obstacle with a score of 12 in the USG analysis is the economic condition of the coffe exporting companies during the pandemic.